Work fatigue among Lebanese physicians and students during the COVID-19 pandemic: validation of the 3D-Work Fatigue Inventory (3D-WFI) and correlates - Elsa Sfeir; Jean-Marc Rabil; Sahar Obeid; Souheil Hallit; Marie-Claude Fadous Khalife (BMC, 2022)
Abstract Background Work fatigue is a work-related condition that affects physicians' health, work attitude safety and performance. Work fatigue affects not only medical workers but can also leave a negative impact on patients. With the burden of the COVID-19 pandemic as well as the economic crisis Lebanese doctors have been facing in the last 2 years, the aim of our study was to validate the 3D-Work Fatigue Inventory (3D-WFI) among Lebanese physicians and assess the rate and correlates of work fatigue (physical, mental and emotional). Methods A cross-sectional study was undertaken through an anonymous self-administered questionnaire between October 2020 and January 2021. The SPSS AMOS software v.24 was used to conduct confirmatory factor analysis (CFA). To validate the 3D-WFI, multiple indices of goodness-of-fit were described: the Relative Chi-square (χ2/df) (cut-off values:< 2-5), the Root Mean Square Error of Approximation (RMSEA) (close and acceptable fit are considered for values < 0.05 and < 0.11 respectively), the Tucker Lewis Index (TLI) and the Comparative Fit Index (CFI) (acceptable values are ≥0.90). Results A total of 401 responses was collected; 66.1, 64.8 and 65.1% respondents had an intermediate to high level of emotional, mental and physical work fatigue respectively. The fit indices obtained in the CFA of the 3D-WFI items fitted well: CFI =0.98, TLI =0.98, RMSEA = 0.05; 95% CI 0.046-0.063; pclose = 0.20) and χ2(136) = 295.76. The correlation coefficients between the three factors (Factor 1 = Physical work fatigue, Factor 2 = Mental work fatigue, Factor 3 = Emotional work fatigue) were adequate as well: Factor 1-Factor 2 (r = 0.70), Factor 1-Factor 3 (r = 0.52) and Factor 2-Factor 3 (r = 0.65). In addition, feeling pressured by long working hours during the pandemic, having more hours of night duty per month, more stressful events in life, and higher depression were significantly associated with more physical and mental work fatigue. Higher depression and having more stressful events in life were significantly associated with more emotional work fatigue. Conclusion Work fatigue in Lebanese physicians seems to be associated with higher level of everyday stress, high work load and depression. Hospitals and local health authorities can use these results for early interventions that aim to reduce work fatigue and ensure the wellbeing of Lebanese physicians.